2019
DOI: 10.15666/aeer/1702_25512569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shade Treatments on Morphology, Photosynthetic and Chlorophyll Fluorescence Characteristics of Soybeans (Glycine Max L. Merr.)

Abstract: In maize soybean intercropping-system maize plants significantly increase the shade density at soybean canopy, and few people studied the threshold level of shade for sustainable production of soybean in this system. This experiment was started to determine the effect of four different shade treatments T75 (75%); T50 (50%); T25 (25%); T0 (0%, control) on morphology, physiology and yield of soybean plants. Relative to T75, treatments T25 and T0 significantly increased the stem diameter and stem breaking strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 52 publications
3
23
0
5
Order By: Relevance
“…In relay‐intercropping system, soybean crop is the late sown crop (Echarte et al, ) and different planting arrangements changed the micro climate of soybean plants especially light (Awal, Koshi, & Ikeda, ), especially when the distance between maize and soybean rows reduced (Yang et al, ). Past reports confirmed that soybean is sensitive to low light conditions and shading environments impaired the yield parameters of soybean (Feng et al, , ; Khalid et al, ). In most of the previous investigations, they examined the impacts of shading and light intensity on the yield parameters of sole‐cropped soybean (Feng et al, ; F. Yang et al, ).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In relay‐intercropping system, soybean crop is the late sown crop (Echarte et al, ) and different planting arrangements changed the micro climate of soybean plants especially light (Awal, Koshi, & Ikeda, ), especially when the distance between maize and soybean rows reduced (Yang et al, ). Past reports confirmed that soybean is sensitive to low light conditions and shading environments impaired the yield parameters of soybean (Feng et al, , ; Khalid et al, ). In most of the previous investigations, they examined the impacts of shading and light intensity on the yield parameters of sole‐cropped soybean (Feng et al, ; F. Yang et al, ).…”
Section: Introductionmentioning
confidence: 78%
“…This reduction in LAI, accumulation of dry matter, and yield of intercropped maize mainly attributed to large intra‐specific competition between maize plants. Whereas, narrow‐wide‐row planting arrangement considerably increased the soybean LAI, dry matter, and seed yield under RI, the increase in intercropped soybean LAI, accumulation of dry matter, and seed yield under narrow‐wide‐row planting arrangement may be due to the higher light transmittance at soybean canopy because soybean crop is sensitive to shading conditions (Khalid et al, ). Importantly, as compared to P4, treatment P1 (narrow‐wide row planting) meaningfully improved the soybean yield by 151% and reduced the maize yield by 12%, maize showed lower yield loss than yield gain of soybean, results are consistent with past reports (Raza et al, ; Yang et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic characteristics are responsive to variation in LAI caused by various leaf excision treatments (T. Liu et al, ; Yang et al, ). Normally, photosynthetic rate improves with the increase in LAI (Khalid et al, ). However, maize plants with greater leaf area receive less sunlight at the middle and lower leaves, which decreases the photosynthetic rate by increasing the leaf senescence (Wei et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main achievements in adopting MSR is the production of higher dry-matter accumulation in relay-intercropped maize plants due to the facilitation and complementary effects of soybean during the cogrowth period (Feng et al, 2019;Yang et al, 2017). This is ascribed to the fact that maize plants exhibit extensive and robust growth during the cogrowth phase (Ahmed et al, 2018), whereas the soybean plants show decreasing growth and dry-matter accumulation with inferior morphological characteristics (Feng et al, 2018;Khalid et al, 2019;Liu et al, 2016;Wu et al, 2017). In this experiment, maize dry matter decreased, and soybean dry matter increased with increasing the gap width between soybean and maize rows from 0.40 to 0.70 m. This reduction in dry matter of intercropped maize is mainly attributed to the large competition between intercrop species in MSR.…”
Section: Effect Of Strip Width Treatments On Crops Yieldsmentioning
confidence: 99%
“…However, soybean in MSR produced lower crop yield than sole soybean because it is planted two months after maize sowing, and the severe competition for available resources with maize plants reduces the initial growth of soybean plants (Fan et al, 2018). Moreover, past studies have confirmed the adverse impacts of shading conditions on soybean morphology (Khalid et al, 2019;Raza, Feng, Iqbal, Ahmed, et al, 2019), physiology (Feng et al, 2018), and dry-matter accumulation (Ahmed et al, 2018;Yang et al, 2014). However, after maize harvesting in MSR, soybean exhibit strong recovery growth (Wu et al, 2016), and the competition for available resources with maize is compensated from the vegetative stage to the flowering stage (Fan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%